Learning history in the context of the cultural identity and orality of the cokwe people - André Rufino , Sapalo; Jílio Icola , Feliberto; Venet Pérez , Maritza (Revista Minerva, 2023)
To socialize the pedagogical strategy to safeguard the interests of the peoples and their originality, in the context of cultural insertion and valorization, which contributes to improve the quality of teaching and learning of history through the incorporation of predominant educational aspects in the educational process. The general method applied is the dialectical-materialist method and the theoretical and empirical level methods are considered. The historical-logical method favors the historical trajectory of the subject in the national context and in the institution in question. Systematization is useful for the trajectory of history as a discipline. The survey allowed the determination of the particularities and regularities in the teaching and learning process. Result: Conception and design of a pedagogical strategy. The strategy lays the foundations that favors and stimulates knowledge, with impact on the formation and permanent renewal of the teacher and students, in the context of the orality of the Cokwe people.
Keywords: Pedagogical strategy; teaching and learning process; orality; knowledge